2018
DOI: 10.5539/mas.v12n12p28
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Warm Mix Asphalt Manufactured with Blast Furnace Slag

Abstract: The study evaluated the response under monotonic loading (Marshall and indirect traction) and the resistance to moisture damage and abrasion of a warm mix asphalt (WMA) manufactured with an additive called HUSIL, when the coarse fraction of the aggregate was replaced by a blast furnace slag (BFS). In conclusion, it is reported that the additive is capable of reducing the manufacturing temperature of the asphalt mixture by 30 ° C. Additionally, the BFS can be used as a partial substitute for the coarse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…However, when the mass was replaced, the adhesive properties of the asphalt-aggregate system worsened. On the basis of a study of a warm mix asphalt (WMA), [28] concluded that BFS can be used as a partial substitute for the coarse fraction of aggregates in WMA. When 21% of the coarse aggregates was replaced with BFS, the mixture's stiffness, resistance to moisture damage, and resistance to abrasion all increased beyond the levels achieved with the control asphalt mixture.…”
Section: Bfs In Asphalt Mixturesmentioning
confidence: 99%
“…However, when the mass was replaced, the adhesive properties of the asphalt-aggregate system worsened. On the basis of a study of a warm mix asphalt (WMA), [28] concluded that BFS can be used as a partial substitute for the coarse fraction of aggregates in WMA. When 21% of the coarse aggregates was replaced with BFS, the mixture's stiffness, resistance to moisture damage, and resistance to abrasion all increased beyond the levels achieved with the control asphalt mixture.…”
Section: Bfs In Asphalt Mixturesmentioning
confidence: 99%